Association of bilaterally suppressed EEG amplitudes and outcomes in critically ill children - Paul, Luisa; Greve, Sandra; Hegemann, Johanna; Gienger, Sonja; Löffelhardt, Verena Tamara; Della Marina, Adela; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Bruns, Nora (Frontiers in Neuroscience, 2024)
Background and objectives: Amplitude-integrated EEG (aEEG) is used to assess electrocortical activity in pediatric intensive care if (continuous) full channel EEG is unavailable but evidence regarding the meaning of suppressed aEEG amplitudes in children remains limited. This retrospective cohort study investigated the association of suppressed aEEG amplitudes in critically ill children with death or decline of neurological functioning at hospital discharge. Methods: 235 EEGs derived from individual patients < 18 years in the pediatric intensive care unit at the University Hospital Essen (Germany) between 04/2014 and 07/2021, were converted into aEEGs and amplitudes analyzed with respect to age-specific percentiles. Crude and adjusted odds ratios (OR) for death, and functional decline at hospital discharge in patients with bilateral suppression of the upper or lower amplitude below the 10th percentile were calculated. Sensitivity, specificity, positive (PPV) and negative predictive values (NPV) were assessed. Results: The median time from neurological insult to EEG recording was 2 days. PICU admission occurred due to neurological reasons in 43 % and patients had high overall disease severity. Thirty-three (14 %) patients died and 68 (29 %) had a functional decline. Amplitude suppression was observed in 48 % (upper amplitude) and 57 % (lower amplitude), with unilateral suppression less frequent than bilateral suppression. Multivariable regression analyses yielded crude ORs between 4.61 and 14.29 and adjusted ORs between 2.55 and 8.87 for death and functional decline if upper or lower amplitudes were bilaterally suppressed. NPVs for bilaterally non-suppressed amplitudes were above 95 % for death and above 83 % for pediatric cerebral performance category Scale (PCPC) decline, whereas PPVs ranged between 22 and 32 % for death and 49 – 52 % for PCPC decline. Discussion: This study found a high prevalence of suppressed aEEG amplitudes in critically ill children. Bilaterally normal amplitudes predicted good outcomes, whereas bilateral suppression was associated with increased odds for death and functional decline. aEEG assessment may serve as an element for risk stratification of PICU patients if conventional EEG is unavailable with excellent negative predictive abilities but requires additional information to identify patients at risk for poor outcomes.